The causes and implications of obstetric malpractice - Jahn Kassim, Puteri Nemie; Mohd Najid, Khadijah (Science Publishing Corporation, 2015)
Obstetrics and Gynaecology (O & G) are among the specialties at high risk of malpractice claims. In particular, obstetric malpractice attracts high incidence of claims as birth injuries are usually serious and devastating. The resulting disabilities and malformation from the injuries tend to be life-long and victims are deprived of years of enjoyment in life, independence and productivity. As these injuries occur on the victims early in life, the costs of medical care are usually enormous. As this imposes stressful and heavy burden on the family members, they tend to resort to litigation as means of procuring monetary compensation. The highest numbers of medical negligence cases in Malaysia involve obstetric injuries and six to seven-figure court awards are now becoming the trend for compensating obstetric malpractice victims. However, proving obstetric malpractice is not an easy task with years of litigation, which eventually may not provide victims with monetary compensation if unsuccessful. Further, the increase in obstetric litigation has triggered higher premium for medical indemnity insurance causing many doctors to leave the subspecialty. Even though the doctor at the end may not be found guilty but the trauma of being sued caused them to suffer difficulties in returning to their work.